Ready-to-use mesoporous mineralized silk fibroin microspheres and preparation method and application thereof

By preparing mesoporous mineralized silk fibroin microspheres, the problem of rapid release and short retention time of BMP-2 controlled release carrier was solved, and the efficient loading and long-term low-volume sustained release of BMP-2 was achieved, which promoted bone regeneration and Repair, providing an efficient and safe treatment plan for bone defects.

CN118634366BActive Publication Date: 2024-12-13ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411111857.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-13
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The existing BMP-2 controlled release carriers have problems such as rapid release, short retention time, and complex carrier components, which are difficult to achieve long-term low-dose sustained release, resulting in poor bone defect treatment effect.

Method used

Mesoporous mineralized silk fibroin microspheres were prepared by bionic mineralization method and critical point drying method to form microspheres with mesoporous pore structure, load BMP-2 and form on the surface. Acupuncture-like calcium phosphate mineralized coating achieves high-efficiency loading and long-term low-volume sustained release.

Benefits of technology

Achieve long-term low-dose sustained release of BMP-2 with a load rate of more than 85% and a cumulative release of about 2% in 4 weeks, avoiding early sudden release, improving bone regeneration and repair effects, and providing an efficient, safe and economical Bone defect treatment plan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118634366B_ABST
    Figure CN118634366B_ABST
Patent Text Reader

Abstract

The present invention provides a ready-to-use mesoporous mineralized silk fibroin microsphere and a preparation method and application thereof. SilMA hydrogel microspheres are prepared by a photocrosslinking oil / water emulsification method, and then dry mesoporous mineralized SilMA microspheres (mSilMA for short) are prepared by combining biomimetic mineralization with a critical point drying method. Silk fibroin materials that are not easily degraded and have good biocompatibility are selected as carriers to solve the problems of easy loss and inability to retain BMP-2 for a long time; biomimetic mineralization forms a calcium phosphate coating to achieve efficient loading and controlled release of BMP-2; critical point drying forms a mesoporous structure, which is conducive to drug loading and release. mSilMA is applied to BMP-2 loading and controlled release, with high protein loading efficiency and long-term low-volume sustained release. The present invention has simple ingredients, mild preparation conditions, and is easy to obtain, providing a new approach for bone defect repair and has broad clinical application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomedical materials, and in particular relates to ready-to-use mesoporous mineralized silk fibroin microspheres and a preparation method and application thereof. Background Art

[0002] BMP-2 (bone morphogenetic protein-2) plays a key role in bone defect repair due to its potent osteogenic capacity. With the aging population and the increasing demand for bone defect treatment, the global market for BMP-2 products is projected to grow from US$480 million in 2022 to US$660 million in 2029. Because the regeneration of damaged bone tissue is a dynamic process involving coordinated cellular and biomolecular responses over weeks, the ability to maintain bioactive BMP-2 within bone defects for extended periods of time holds promise for improving bone healing. However, current BMP-2 clinical products suffer from short in vivo retention, severe side effects at high doses, and the proinflammatory potential of early burst release. Therefore, the development of simple, safe, and ready-to-use delivery vehicles that can deliver long-term, low-dose sustained release of BMP-2 to promote bone regeneration is a crucial challenge in the field of bone repair.

[0003] Medtronic's Infuse BoneGraft (a BMP-2-loaded absorbable collagen sponge scaffold) holds the largest market share of BMP-2 bone implants worldwide. The primary limitation of BMP-2 delivery via sponge collagen is its rapid release, which has been extensively demonstrated in vitro, in vivo, and clinically. 40%-90% of the BMP-2 is released in an initial burst. After one to two weeks, only 10% or less of the BMP-2 remains at the implant site, leading to the use of higher doses and exacerbating local and systemic adverse reactions (inflammation, heterotopic ossification, and cysts).

[0004] Prominent domestic BMP-2 bone implants primarily focus on calcium-phosphate-based materials. Examples include Shanghai Ruibang Biotechnology's self-setting calcium phosphate active artificial bone, which consists of a calcium phosphate salt (powder) and a curing solution (a soluble phosphate aqueous solution). These two components are pre-mixed into a calcium phosphate artificial bone paste. Hangzhou Jiuyuan Gene's "Bone Guide" utilizes pharmaceutical gelatin, soy lecithin, and hydroxyapatite as carriers to form a complex with BMP-2. Yantai Zhenghai Biotechnology's active artificial bone combines BMP-2 with hydroxyapatite and collagen derived from decellularized bovine bone. Genetic engineering allows for the specific binding of BMP-2 to the collagen material, reducing BMP-2 dosage. While calcium-phosphate materials offer significant advantages in osteoinduction and osteoconduction, they degrade rapidly in vivo and lack the ability to sustain sustained release of BMP-2.

[0005] In addition to the collagen-based and calcium-phosphorus-based BMP-2 bone implants that have been clinically transformed, many new BMP-2 carriers that promote bone regeneration have also been reported in the literature. However, their composition is complex, the preparation process is complicated, they are not easy to obtain immediately, and their clinical transformation is slow. For example, Liu et al. prepared a PLGA scaffold, treated it with plasma technology to increase its surface hydrophilicity, then immersed it in a mixture of zwitterionic monomers, crosslinkers, and photoinitiators. UV-curing was used to form a zwitterionic hydrogel coating on the surface of the PLGA scaffold. The PLGA / zwitterionic hydrogel was further immersed in a calcium-phosphate mineralization solution to form calcium phosphate mineralization on the scaffold surface. The mineralized PLGA / zwitterionic hydrogel was freeze-dried to form a scaffold capable of low-volume sustained release of BMP-2. This design achieves controlled release of BMP-2 through the synergistic effect of the charge interaction between the zwitterionic hydrogel and BMP-2 and the strong affinity of the calcium phosphate mineralization for BMP-2 (Liu P, Bao T, Sun L, et al. In situ mineralized PLGA / zwitterionic hydrogel composite scaffold enables high-efficiency rhBMP-2 release for critical-sized bone healing[J]. Biomaterials Science, 2012). 2022); however, the PLGA scaffold has the following disadvantages: First, the multi-step preparation process is cumbersome and complex, time-consuming, and costly, making it unsuitable for large-scale production and rapid application. Second, the structure and performance of the scaffold may be affected by the multiple processing steps, resulting in stability and reproducibility issues. Furthermore, the preparation process involves multiple components and complex processes, which may also affect the biocompatibility and biodegradability of the scaffold. Therefore, this PLGA scaffold cannot achieve the effects of rapid preparation and efficient mass production, making it difficult to quickly meet the immediate needs of bone defect repair in actual clinical applications, and its role in rapid translation for clinical treatment is limited.

[0006] Therefore, there is an urgent need to find a biomaterial carrier that can solve the problems of rapid release, short retention time, and complex carrier components of existing BMP-2 controlled-release carriers. It has the characteristics of simple preparation process, low cost, and good biocompatibility. It can achieve long-term, low-volume sustained release of BMP-2, avoid early sudden release, maintain its biological activity, promote bone regeneration, and has good clinical transformation potential and application prospects, providing a more effective solution for the treatment of bone defects. Summary of the Invention

[0007] To address the problems existing in the prior art, the present invention provides ready-to-use mesoporous mineralized silk fibroin microspheres, as well as their preparation and application. Using silk fibroin methacrylamide as the raw material, the prepared microspheres (mSilMA) were successfully prepared using a biomimetic mineralization method and a critical point drying method. Silk fibroin is a regularly oriented fiber structure formed by the hierarchical assembly of nanofibrils. It contains a large number of polar amino acids. These hydrophilic and polar groups can tightly bind to positive and negative ions, inducing the nucleation and growth of inorganic substances on the silk fibroin template. The mSilMA microspheres prepared in this invention achieve an effective loading rate of over 85% for BMP-2 (500 ng) per milligram. In vitro sustained-release assays revealed that the mSilMA microspheres can sustain low-level sustained-release of BMP-2, with a cumulative release of approximately 2% of BMP-2 over four weeks in vitro. This achieves long-term, low-level release of BMP-2 in vitro without the occurrence of an early burst release.

[0008] In order to achieve the above object, the present invention adopts the following scheme:

[0009] On the one hand, the present invention provides a ready-to-use mesoporous mineralized silk fibroin microsphere, wherein the main component of the ready-to-use mesoporous mineralized silk fibroin microsphere has a fiber structure, the microsphere has a mesoporous channel structure, and the surface of the microsphere includes a mineralized coating.

[0010] Furthermore, the main component includes silk fibroin; the silk fibroin is silk fibroin methacrylamide.

[0011] Furthermore, the mineralized coating is needle-shaped calcium phosphate; and the pore size of the mesoporous channel is 5-50 nm.

[0012] To address the numerous problems currently encountered in the field of bone repair with controlled-release carriers of BMP-2, such as rapid release, short retention time, and complex carrier components, the present invention proposes ready-to-use mesoporous mineralized silk fibroin microspheres capable of long-term, low-volume sustained release of bone morphogenetic protein, based on the natural fiber structure of silk fibroin. By using silk fibroin methacrylamide as the main component and utilizing its fiber structure properties, a specific preparation method is employed to form a mesoporous channel structure in the microspheres, and a needle-shaped calcium phosphate mineralized coating is generated on the surface of the microspheres.

[0013] The microspheres produced by the present invention have a BMP-2 loading efficiency exceeding 85%, and can achieve long-term, low-dose sustained release of BMP-2, with a cumulative release of only about 2% over four weeks in vitro. Furthermore, the microspheres exhibit excellent biocompatibility and stability, remaining stable and long-term within the implanted bone defect site, continuously promoting bone repair and regeneration, providing a highly effective and promising solution for bone defect treatment.

[0014] Furthermore, the ready-to-use mesoporous mineralized silk microspheres are loaded with active proteins, and the active proteins include any one or more of BMP-2, VEGF, FGF, and TGF-β.

[0015] Furthermore, the active protein is BMP-2.

[0016] The ready-to-use mesoporous mineralized silk microspheres are loaded with active proteins, including bone morphogenetic protein-2 (BMP-2), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), transforming growth factor-β (TGF-β), etc.

[0017] In the present invention, the microspheres are particularly selected to be loaded with BMP-2 because the existing BMP-2 controlled-release carriers have problems such as rapid release, short retention time, and complex carrier components. When the microspheres of the present invention are used to load BMP-2, the loading efficiency of BMP-2 can be significantly improved, and its long-term, low-volume sustained release can be achieved. Specifically, the mesoporous structure of the microspheres increases the specific surface area, providing more binding sites for BMP-2, thereby increasing the loading capacity. At the same time, the mineralized coating on the surface of the microspheres effectively controls its release rate through interaction with BMP-2, avoiding early sudden release, allowing BMP-2 to continue to play a role over a long period of time, and promoting the regeneration and repair of bone tissue. In addition, the good biocompatibility and stability of silk fibroin ensure the safety and effectiveness of the microspheres in vivo, providing a kind of efficient and reliable solution for the treatment of bone defects.

[0018] In some embodiments, the present invention compares and screens the BMP-2 protein loading rate and long-term low-volume sustained-release ability of microspheres with different main components, different drying methods, different mineralization methods, different mineralization concentrations, undried microspheres, and unmineralized microspheres. The experimental results show that only when silk fibroin methacrylamide is used as the main component, the critical drying method is used for drying, the Ca / P method is used, and the mineralization solution concentration is 1 times the Ca / P mineralization solution, can mSilMA microspheres with surface-penetrating mesoporous channels and complete structure be successfully prepared, and the BMP-2 protein loading rate can reach more than 85%, while BMP-2 can be continuously released in low amounts, with a cumulative release of about 2% of BMP-2 in vitro for 4 weeks; and when any of the conditions is replaced arbitrarily, the effect of the present invention cannot be achieved.

[0019] In the field of bone repair, achieving long-term, low-dose sustained release of bone morphogenetic protein (BMP-2) has been a critical challenge. This study aims to overcome this challenge by using silk fibroin as a raw material and combining biomimetic mineralization with critical point drying to successfully prepare ready-to-use mesoporous mineralized silk fibroin microspheres (mSilMA).

[0020] Silk fibroin, a raw material that is the foundation of the present invention, has a unique fiber structure and excellent biocompatibility. Without this raw material or replacing it with other materials, it would not provide a suitable carrier for the subsequent mineralization and drying steps, and would not be able to achieve BMP-2 loading and controlled release.

[0021] The biomimetic mineralization method (calcium chloride / phosphoric acid-ammonia reaction method) is essential in the preparation process. This method forms a calcium phosphate mineralized coating on the surface of silk fibroin microspheres, leveraging calcium phosphate's strong affinity for BMP-2 for efficient loading while significantly reducing the release rate of BMP-2. Without the biomimetic mineralization step or using other mineralization methods and concentrations, the mineralized coating cannot be formed. Even with silk fibroin as the raw material and the critical point drying method, the lack of strong affinity for BMP-2 and its controlled release effect prevents effective loading and long-term stable controlled release of BMP-2, thus failing to achieve a long-term, low-dose sustained release effect.

[0022] Critical point drying is a key step in forming a mesoporous structure. The mesoporous channel structure can provide more binding sites for BMP-2, facilitating the retention and sustained release of cytokines and enhancing the interaction between the microspheres and the body. If only silk fibroin raw materials and biomimetic mineralization methods are used, without critical point drying to form a mesoporous channel structure, the cytokine binding sites are limited, making it impossible to achieve efficient loading and slow, sustained release of BMP-2. When other drying methods are used, based on the same technical solutions of the present invention, mesoporous channels cannot be formed at all.

[0023] In summary, only by using silk fibroin as raw material and synergistically adopting the biomimetic mineralization method (calcium chloride / phosphoric acid-ammonia water reaction method) and critical point drying method, all three of which are indispensable, can the optimal mSilMA be successfully prepared, achieving long-term, low-volume sustained release of BMP-2, high loading efficiency and good biocompatibility, providing an ideal material for bone repair.

[0024] In another aspect, the present invention provides a method for preparing ready-to-use mesoporous mineralized silk fibroin microspheres, comprising the following steps:

[0025] (1) Preparation of SilMA hydrogel microspheres;

[0026] (2) Mineralizing SilMA hydrogel microspheres;

[0027] (3) drying the mineralized SilMA hydrogel microspheres to obtain dry mesoporous mineralized SilMA microspheres;

[0028] In step (1), SilMA hydrogel microspheres are prepared by UV-crosslinking oil / water emulsification and mechanical stirring; in step (2), mineralization is carried out by the Ca / P method; and in step (3), drying is carried out by critical point drying. Gelatin methacrylamide hydrogel microspheres (GelMA) undergo the same ethanol gradient dehydration and critical point drying, but do not form a surface-penetrating mesoporous structure, but rather a non-porous structure; whereas the surface of the SilMA microspheres forms an interconnected mesoporous channel structure. Therefore, it can be preliminarily determined that not all materials can form mesopores through critical point drying.

[0029] In some embodiments, different preparation methods were screened for the preparation of SilMA. Experimental results demonstrated that the SilMA prepared using the UV-crosslinked oil / water emulsion method (mechanical stirring) of the present invention significantly improved both microsphere yield and microsphere sphericity, offering significant advantages over microspheres prepared using photocrosslinked 3D printing technology in terms of both yield and sphericity. Microspheres prepared using photocrosslinked 3D printing tend to stick together and become difficult to separate, and exhibit poor sphericity, generally forming cylindrical shapes. Furthermore, the mechanical stirring method employed in the present invention allows for the successful preparation of microspheres with a particle size range of 1 μm to 1000 μm by varying parameters such as the oil / water ratio and stirring speed. However, photocrosslinked 3D printing technology cannot print microspheres below 100 μm, and can only print microspheres of specific sizes, such as 200 μm and 400 μm. Furthermore, microsphere yield is limited by the volume of the printing ink and the size of the printable stage.

[0030] Therefore, it is preferred to use the UV-crosslinked oil / water emulsification method (mechanical stirring) to prepare SilMA, which has the best yield, sphericity, controllable particle size range and other properties, can better meet the needs of practical applications, and lay a solid foundation for the subsequent preparation of mSilMA with excellent performance.

[0031] In some embodiments, to obtain the optimal microspheres of the present invention capable of long-term, low-dose sustained-release of BMP-2, the main components of the microspheres were first screened. Silk fibroin methacrylamide and gelatin methacrylamide were used as the main components of the microspheres, respectively, to prepare GelMA microspheres and SilMA microspheres. Scanning electron microscopic results showed that after the same ethanol gradient dehydration and critical point drying, the GelMA hydrogel microspheres did not form a surface-penetrating mesoporous structure, but rather a non-porous structure. In contrast, the SilMA microspheres formed a structure of interconnected mesoporous channels on their surfaces. This preliminarily indicates that not all materials can form mesopores through critical point drying. Based on the above results, the inventors speculate that it is precisely because silk fibroin has an original fiber structure that its own fiber network can be reproduced through critical point drying; gelatin itself does not have a fiber structure. At the same time, during the ethanol gradient dehydration process, as water is lost, the hydrogel network structure of gelatin itself gradually becomes dense, and then through critical point drying, the fiber network structure can no longer appear, and the surface is dense and non-porous; therefore, it is speculated that if the material itself has a fiber structure, a porous structure can be generated through critical point drying; if the material itself does not have a fiber structure, then a porous structure cannot be generated through critical point drying.

[0032] In the present invention, the mesoporous structure is crucial for preparing hydrogel microspheres capable of long-term, low-dose sustained release of BMP-2. Mesopores significantly increase drug loading, and their interconnected mesoporous channels facilitate the loading and slow, sustained release of cytokines, avoiding sudden release, extending the duration of BMP-2 action, improving BMP-2 utilization efficiency and therapeutic efficacy, and providing stable support for bone repair. Furthermore, the mesoporous structure facilitates the exchange of substances and information between the microspheres and the surrounding environment, promoting cell growth and proliferation within the interstitial spaces of the microspheres and improving their adaptability and biocompatibility within the body.

[0033] Therefore, SilMA, which can form mesopores, is preferred as the main component of the microspheres to achieve more ideal drug loading and controlled release effects, providing strong technical support and innovative ideas for the development of fields such as bone tissue engineering.

[0034] In some embodiments, during the preparation of SilMA microspheres, drying methods for the SilMA hydrogel microspheres were screened. Experimental results showed that the dry SilMA microspheres prepared using the critical point drying method exhibited no adhesion and had uniformly distributed mesopores on the microsphere surface. This uniform mesoporous structure facilitates drug loading and sustained release, providing a more stable and controllable release environment for drugs such as BMP-2, thereby better exerting the effects of BMP-2 and improving therapeutic efficacy. In contrast, the dry SilMA microspheres prepared using the freeze-drying method not only lacked mesopores on the microsphere surface, limiting BMP-2 loading and sustained release performance, but also exhibited adhesion between microspheres, resulting in a rough surface. This rough surface and adhesion may affect the dispersibility and stability of the microspheres, and thus their effectiveness in practical applications. Therefore, the critical point drying method is preferred for preparing dry SilMA microspheres.

[0035] In some embodiments, different mineralization methods were screened during the preparation of mSilMA microspheres. Experimental results show that the Ca / P method can form a more uniform and denser calcium-phosphate mineralized coating on the surface of SilMA microspheres. The more uniform and denser calcium-phosphate mineralized coating can enhance the stability and mechanical strength of the microspheres, improve the compatibility and binding ability of the microspheres with bone tissue, and help better promote bone regeneration and repair processes. In addition, the uniform and high-density coating can more effectively control the release rate of BMP-2, providing a more stable loading and release environment for BMP-2, thereby improving the therapeutic effect of BMP-2. Therefore, the Ca / P method is preferred as the mineralization method for SilMA microspheres.

[0036] Furthermore, the mineralization concentration is 1 times Ca / P mineralization solution, and in the 1 times Ca / P mineralization solution, the molar ratio of calcium chloride to phosphoric acid is 1.5-2.0.

[0037] At the same time, in some embodiments, in the process of preparing mineralized SilMA hydrogel microspheres using the Ca / P method, the concentrations of different Ca / P mineralizing solutions were screened, and the effects of different Ca / P mineralizing solution concentrations on the SilMA microspheres and the surface calcium-phosphate mineralization layer were studied. The experimental results show that, while keeping other conditions unchanged, increasing the concentration of the Ca / P mineralizing solution will lead to the destruction of the microsphere structure. The calcium-phosphate coating still maintains a needle-like structure. As the concentration of the Ca / P mineralizing solution increases, the coating density increases. However, 5 times and 10 times the Ca / P mineralizing solution significantly damage the microsphere structure. Therefore, 1 times the Ca / P mineralizing solution is preferred. At this concentration, the intact structure of the microspheres is retained, and a relatively evenly distributed needle-like calcium-phosphate coating can be present on the surface of 20% SilMA microspheres. At the same time, the mesoporous channels of the microspheres themselves are not completely blocked by the needle-like calcium-phosphate coating.

[0038] Moreover, at a Ca / P mineralization solution concentration of 1, the pore size of the dry mSilMA surface after mineralization and critical drying will be further reduced. This has the following advantages: (1) Better controlled release performance: smaller pore size can more effectively load and control the release rate and amount of drugs or cytokines, so that they can be released continuously and stably for a longer time, thereby improving the therapeutic effect; (2) Enhanced stability: smaller pore size may make the microsphere structure more stable, reduce the impact of the external environment on the internal loaded substance, and improve the stability of the microspheres during storage and use; (3) Improved selectivity: It can more selectively allow molecules of a specific size to pass through or be adsorbed, thereby achieving more accurate drug loading or dissociation; (4) Reduced burst release: Reduce the sudden large-scale release of drugs in the initial stage, making drug release more uniform and controllable; Therefore, it can be seen that in the present invention, mineralization treatment is an indispensable step. Only by mineralizing the SilMA hydrogel microspheres and using the Ca / P mineralization method with low calcium and phosphorus concentrations can the best mSilMA be prepared, achieving the best effect of optimizing the physical properties of the microspheres and the controlled release performance of the drug, and providing a more ideal material choice for applications in related fields such as bone repair.

[0039] In some embodiments, to verify the necessity of the mineralization step for the preparation of mSilMA according to the present invention, this example also focused on comparing the in vitro controlled release of BMP-2 between 20% mSilMA microspheres and 20% SilMA microspheres. The experimental results demonstrated that 20% mSilMA microspheres sustained low-level BMP-2 release, with a cumulative release of approximately 2% of BMP-2 over four weeks in vitro. However, 20% SilMA microspheres failed to achieve long-term BMP-2 release, reaching a plateau release after approximately three weeks. This may be due to a certain degree of equilibrium between drug adsorption and dissolution in the mesopores, resulting in incomplete release.

[0040] Preferably, in the 1x Ca / P mineralization solution, the molar ratio of calcium chloride to phosphoric acid is 1.5-1.7.

[0041] Furthermore, the immersion time of the mineralizing solution is 12 hours to 48 hours; in the Ca / P method, the volume fraction of the ammonia solution is 10% to 20%, and the ammonia solution action time is 30 minutes to 2 hours.

[0042] Furthermore, in step (1), the concentration of the SilMA solution is 10%-30%; the dissolution temperature of the SilMA is 25°C-45°C; LAP solution is added to the SilMA solution as the aqueous phase, and the aqueous phase and the oil phase are stirred and mixed, and the final concentration of the LAP aqueous solution is: 0.1%-0.5%; the volume ratio of the oil phase to the aqueous phase is 1:1-10:1; in the oil phase, the mass ratio of Span 80 to liquid paraffin is 1:10-1:30; the stirring temperature is 25°C-45°C; and the stirring time and UV irradiation time are 5-15 minutes.

[0043] The LAP is lithium phenyl-2,4,6-trimethylbenzoylphosphinate.

[0044] In some embodiments, SilMA microspheres were prepared using a photocrosslinking oil / water emulsion method followed by critical drying using SilMA solutions of varying concentrations. Statistical analysis of their swelling properties and surface pore sizes revealed that, on the one hand, 10% SilMA microspheres exhibited the strongest water absorption and swelling capacity, but were susceptible to swelling and rupture upon immersion within a week, resulting in loss of structural integrity. This suggests insufficient stability and unsuitability for subsequent processing. On the other hand, there was no significant difference in water absorption and swelling capacity between 20% and 30% SilMA microspheres. Furthermore, scanning electron microscopy revealed that the 10% SilMA microspheres had the largest surface pore size, with an average pore size of approximately 100 nm. The 20% SilMA microspheres had a surface pore size of approximately 20 nm, while the 30% SilMA microspheres had an average surface pore size of approximately 5 nm. The molecular diameter of BMP-2 is approximately 10 nm. Combined with the partial effect of subsequent mineralization on the surface pore size of the SilMA microspheres, it is speculated that the pore structure of the 30% SilMA microspheres after mineralization is not conducive to BMP-2 loading. 20% SilMA microspheres, on the other hand, can both physically adsorb BMP-2 and, to a certain extent, limit its rapid release, contributing to a better controlled-release effect. Therefore, considering the swelling properties and surface pore size distribution of SilMA microspheres of varying concentrations, 20% SilMA microspheres demonstrated a more balanced and ideal performance in terms of stability, BMP-2 loading, and controlled release. Therefore, 20% SilMA microspheres were preferred for the next step of biomimetic mineralization.

[0045] Preferably, the dissolution temperature of the SilMA is 25°C-30°C; and the stirring temperature is 25°C-30°C.

[0046] Furthermore, in the step (3), a gradient ethanol aqueous solution is used for dehydration, the microspheres are immersed in the ethanol aqueous solution for 15-30 minutes, and the critical point drying time is 3 hours to 5 hours.

[0047] Preferably, the critical point drying time is 3-5 hours.

[0048] In another aspect, the present invention provides a use of ready-to-use mesoporous mineralized silk fibroin microspheres for preparing a preparation for improving bone repair ability or promoting bone regeneration, wherein the ready-to-use mesoporous mineralized silk fibroin microspheres are prepared by the preparation method described in any one of the above technical solutions.

[0049] On the other hand, the present invention provides a ready-to-use mesoporous mineralized silk fibroin microsphere for preparing a preparation for improving the long-term low-dose sustained release ability of BMP-2 or reducing the burst release ability of BMP-2. The ready-to-use mesoporous mineralized silk fibroin microsphere is prepared by the preparation method described in any one of the above technical schemes.

[0050] In another aspect, the present invention provides a use of ready-to-use mesoporous mineralized silk fibroin microspheres for preparing a preparation for improving the protein loading rate of BMP-2, wherein the ready-to-use mesoporous mineralized silk fibroin microspheres are prepared by the preparation method described in any one of the above technical solutions.

[0051] On the other hand, the present invention provides a use of silk fibroin for preparing a preparation for improving the long-term, low-dose sustained-release ability of BMP-2 or reducing the burst-release ability of BMP-2. In the preparation, silk fibroin is used as a raw material to prepare microspheres, and the microspheres are prepared using the preparation method described in any one of the above technical solutions.

[0052] In another aspect, the present invention provides a use of silk fibroin for preparing a preparation for improving the protein loading rate of BMP-2, wherein the preparation uses silk fibroin as a raw material to prepare microspheres, and the microspheres are prepared using the preparation method described in any one of the above technical solutions.

[0053] The beneficial effects of the present invention are:

[0054] 1. The present invention provides a ready-to-use mesoporous mineralized silk fibroin microsphere, a preparation method and application thereof, wherein SilMA hydrogel microspheres are prepared by a photocrosslinking oil / water emulsification method. This method is simple to operate, easy to control, and can prepare a large number of microspheres with stable performance. The SilMA hydrogel microspheres are converted into mSilMA by combining a biomimetic mineralization method and a critical point drying method. The preparation process has mild conditions and will not damage the structure and performance of the microspheres, which is conducive to large-scale production and application. The ready-to-use dry mesoporous mineralized silk fibroin microspheres prepared by the present invention have a relatively simple composition, comprising only silk-based microspheres and a mineralized coating on the surface of the microspheres.

[0055] 2. The present invention uses silk fibroin material that is not easily degraded and has good biocompatibility as a delivery carrier for BMP-2. The prepared SilMA microspheres are not easily degraded, can stably exist at the implantation site of the bone defect, and continuously release BMP-2, avoiding the problems of rapid loss of BMP-2 caused by easily degradable materials, inflammation caused by early large-scale release, and inability to achieve long-term therapeutic effects, thereby providing long-term and stable support for bone repair; at the same time, by performing biomimetic mineralization on the surface of the SilMA microspheres to form a calcium phosphate mineralized coating, on the one hand, efficient loading is achieved by utilizing the strong affinity of calcium phosphate substances for BMP-2, and on the other hand, the release rate of BMP-2 is greatly reduced, solving the problem that simple calcium phosphate materials are easily degraded and cannot release BMP-2 in a controlled manner for a long time, so that BMP-2 can play a long-term and stable role, promoting bone tissue regeneration and repair; and the critical point drying method is used to form a through-mesoporous pore structure in the SilMA microspheres, which provides an ideal structural basis for the loading and controlled release of drugs and proteins. Drugs or proteins can be captured in the mesopores by physical adsorption and released by diffusion, further enhancing the controlled release performance of the microspheres.

[0056] 3. In the present invention, the prepared mSilMA is applied to the loading and controlled release of BMP-2, and its protein loading efficiency can reach more than 85%, and the cumulative release in 4 weeks is only about 2%, realizing the long-term, low-volume sustained release of BMP-2; the controlled-release performance can effectively maintain the effective concentration of BMP-2 in the local area, reduce the dosage and frequency of drug use, reduce the cost of treatment and potential side effects, and provide an efficient, safe and economical solution for the treatment of bone defects. It also provides an innovative, efficient and broadly applicable technical means for the field of bone defect repair, which is of great significance for improving the treatment effect of bone defects and improving the quality of life of patients. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The present invention provides a preparation process for dry mesoporous mineralized silk fibroin methacrylamide microspheres (mSilMA).

[0058] Figure 2 The surface morphology of GelMA microspheres and SilMA microspheres after critical point drying under a scanning electron microscope.

[0059] Figure 3 The surface morphology of dry SilMA microspheres prepared by freeze drying and critical point drying methods.

[0060] Figure 4 The structure and content results of calcium phosphate substances formed on the surface of SilMA microspheres using different mineralization methods.

[0061] Figure 5The effects of three concentrations of Ca / P mineralization solution on the structure and surface mineralization coating of 20% SilMA microspheres.

[0062] Figure 6 A in FIG is the nitrogen physical adsorption test of dry mesoporous 20% SilMA microspheres (abbreviated as 20% SilMA).

[0063] Figure 6 Figure B is the nitrogen physical adsorption test of dry mesoporous mineralized 20% SilMA microspheres (abbreviated as 20% mSilMA).

[0064] Figure 6 C in the figure is the pore size distribution results of 20% mSilMA microspheres and 20% SilMA microspheres.

[0065] Figure 7 A in the figure is the morphological difference between 20% mSilMA microspheres and 20% SilMA microspheres.

[0066] Figure 7 B in FIG is the difference in the in vitro controlled release ability of BMP-2 between 20% mSilMA microspheres and 20% SilMA microspheres.

[0067] Figure 8 A in the figure is the swelling performance results of 10%, 20%, and 30% dry mesoporous SilMA microspheres.

[0068] Figure 8 B in the figure is the surface pore size distribution of 10%, 20%, and 30% SilMA microspheres obtained by statistical analysis of scanning electron microscopy results (obtained by critical drying).

[0069] Figure 9 Surface morphology of 10%, 20%, and 30% dry SilMA microspheres (obtained by critical drying).

[0070] Figure 10 A in the figure is a light microscopy image of 20% SilMA hydrogel microspheres prepared by the photocrosslinking oil / water emulsification method (mechanical stirring).

[0071] Figure 10 Figure B is a light microscopy image of 20% SilMA hydrogel microspheres prepared by photo-crosslinking 3D printing technology. DETAILED DESCRIPTION

[0072] The present invention is described in detail below with reference to the embodiments. It should be noted that the embodiments described below are intended to facilitate understanding of the present invention and do not have any limiting effect on the present invention.

[0073] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0074] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0075] Glossary of relevant terms:

[0076] 1. Bionic mineralization: In the field of artificial material synthesis, biomimetic mineralization regulates the nucleation and growth of minerals such as calcium carbonate and calcium phosphate to obtain inorganic or inorganic / organic composite materials with complex advanced structures and special biological functions.

[0077] 2. Critical point drying method: To prevent slight deformation of the sample due to the rapid movement of the water interface during drying, the liquid in the sample is removed in a critical state where there is no gas-liquid interface. In traditional drying methods, the liquid is directly converted into gas under high temperature conditions, which will produce a certain change in surface tension and may destroy the fine structure of the sample. For special samples, such as sol-gels, biological samples, and structurally unstable porous materials, using traditional drying methods to pre-treat the sample will cause damage to the sample structure. In contrast, using the critical point drying method, the medium adopts a phase change method of liquid carbon dioxide-supercritical carbon dioxide-gas carbon dioxide, which reduces the surface stress of the interface to zero and preserves the fine structure of the sample.

[0078] 3. The main process of critical point drying samples: After the samples are dehydrated in a gradient of 30%-50%-70%-90%-100% ethanol-water solution, they are placed in a critical point drying device (a high-pressure sealed container), injected with liquid carbon dioxide, and dried under a critical state of 31°C and 72.8 atmospheres.

[0079] Example 1 The best ready-to-use dry mesoporous mineralized silk fibroin microspheres of the present invention and their preparation method

[0080] 1. Research ideas and process of the ready-to-use dry mesoporous mineralized silk fibroin microspheres of the present invention

[0081] In the current field of bone repair, BMP-2, as a key bone morphogenetic protein, plays an important role in promoting bone regeneration. However, existing BMP-2 controlled-release carriers suffer from issues such as rapid release, short retention time, and complex carrier components, which severely limit their effectiveness in clinical applications.

[0082] In light of this, the present invention is dedicated to finding a new solution that can effectively address these issues. After in-depth research and extensive experimentation, combined with a thorough understanding of silk fibroin, calcium-phosphate materials, and mesoporous structures, the present invention proposes an innovative concept for preparing ready-to-use mesoporous mineralized silk fibroin-based microspheres. This innovative concept, combined with a method for preparing ready-to-use mesoporous mineralized silk fibroin microspheres capable of long-term, low-volume sustained release of bone morphogenetic protein, ultimately yields ready-to-use mesoporous mineralized silk fibroin microspheres.

[0083] Silk fibroin is a natural, high-molecular-weight, fibrous protein extracted from silkworms. It exhibits tunable mechanical properties, controllable degradation, low immunogenicity, and is readily available at low cost. A variety of silk-based biomaterials have been approved for clinical use in my country, including silk-based ligament grafts and long-term bioresorbable surgical meshes, demonstrating the potential for clinical translation of silk-based scaffolds. Kaplan et al. prepared silk-fibroin-coated hydroxyapatite particles, using a silk-fibroin coating to bind BMP-2. However, this method failed to achieve long-term, low-volume sustained release of BMP-2, failing to meet the requirements for long-term, stable release. The sustained release duration was short, making it difficult to achieve the desired therapeutic effect. (Ding ZZ, Fan ZH, Huang XW, et al. Bioactive natural protein–hydroxyapatitenano carriers for optimizing osteogenic differentiation of mesenchymal stem cells[J]. Journal of Materials Chemistry B, 2016.)

[0084] Calcium-phosphite materials are attractive matrices for the controlled release of BMP-2. They can reversibly bind to proteins, interacting physicochemically and electrostatically with the protein's characteristic conformation and amino groups. Studies have found that mineralized collagen scaffolds release approximately 80% of BMP-2 in vitro over 14 days. However, due to the susceptibility of collagen scaffolds to degradation, the retention of BMP-2 cannot be prolonged, making it difficult to achieve stable and controlled release over a long period of time, making it difficult to meet the requirements of certain applications requiring long-term sustained release of BMP-2. (Yang HS, La WG, Bhang SH, et al. Apatite-coated collagen scaffold for bonemorphogenetic protein-2 delivery[J]. Tissue Engineering Part A, 2011)

[0085] Mesoporous materials have attracted considerable attention in the field of drug delivery due to their regular pore structure, relatively narrow pore size distribution, and large specific surface area. Drugs can be captured within the mesopores through an impregnation adsorption process and released by diffusion. Liu et al. used a mesoporous bioactive glass scaffold to adsorb BMP-2, but the initial release reached 27% after one day; therefore, it can be seen that the mesoporous structure is not effective in reducing early burst release. Moreover, the adsorption / dissolution of drugs in the mesoporous structure tends to reach equilibrium within a certain period of time, resulting in incomplete release of BMP-2, which cannot fully exert the drug's effect and makes it difficult to achieve a stable, sustained, and complete release of BMP-2. (Liu Y, Yang Z, Wang L, et al. Spatiotemporal ImmunomodulationUsing Biomimetic Scaffold Promotes Endochondral Ossification-mediated BoneHealing[J]. Advanced Science, 2021 / / Le TT, et al. Delivery of poorly soluble drugs via mesoporous silica: Impact of drug overloading on release and thermal profiles[J]. Pharmaceutics, 2019 / / He S, Pan H, Zhang J. Advances of typical mesoporous materials and the application in drug delivery[J]. Materials Research Express, 2023.)

[0086] Therefore, in this study, ready-to-use dry mesoporous mineralized silk fibroin microspheres (mSilMA) were prepared using silk fibroin methacrylamide (SilMA) as the raw material, utilizing a combination of biomimetic mineralization and critical point drying methods. Silk fibroin is a regularly oriented fibrous structure formed by the hierarchical assembly of nanofibrils. It contains numerous polar amino acids. These hydrophilic and polar groups can tightly bind to positive and negative ions, inducing the nucleation and growth of inorganic substances on the silk fibroin template. The mSilMA prepared in this invention achieves an effective loading rate of over 85% for BMP-2 (500 ng) per milligram. In vitro sustained-release assays revealed that the mSilMA microspheres can sustain low-level BMP-2 release, with a cumulative release of approximately 2% over four weeks, demonstrating long-term, low-level BMP-2 sustained release.

[0087] 2. Preparation method of ready-to-use mesoporous mineralized silk fibroin microspheres

[0088] The present invention provides an optimal preparation method for ready-to-use mesoporous mineralized silk fibroin microspheres capable of long-term, low-volume sustained release of BMP-2, which specifically comprises the following steps:

[0089] 1. Preparation of SilMA hydrogel microspheres by photocrosslinking oil / water emulsion method

[0090] SilMA was dissolved in double-distilled water at room temperature to obtain a 20% (w / v) SilMA solution. A specific volume of LAP solution (UV photoinitiator: lithium phenyl (2,4,6-trimethylbenzoyl) phosphate) was added as the aqueous phase to a final concentration of 0.25% (w / v). The oil phase consisted of liquid paraffin and Span 80 in a 1:20 ratio. The aqueous phase was added dropwise to the oil phase at a 5:1 oil / water ratio. The mixture was stirred at 400 rpm at room temperature and UV irradiated during stirring. After 10 minutes, stirring and irradiation were stopped, and the mixture was allowed to settle to the bottom of the beaker. The supernatant (oil phase) was discarded, and the mixture was washed three times with 50% isopropanol, twice with 75% isopropanol, and once with 80% isopropanol. The mixture was then rinsed three times with copious amounts of water. The mixture was allowed to settle to the bottom of the beaker. The supernatant (water) was discarded and the microspheres were harvested by filtration.

[0091] wherein, the concentration of the SilMA solution is 10%-30%; the dissolution temperature of the SilMA is 25°C-45°C, and in this embodiment, preferably 25°C-30°C; the final concentration of the LAP aqueous solution is: 0.1%-0.5% (W / V%); in the oil phase, the mass ratio of Span 80 to liquid paraffin is 1:10-1:30; the volume ratio of the oil phase to the aqueous phase is 1:1-10:1; the stirring temperature is 25°C-45°C, and in this embodiment, preferably 25°C-30°C; the stirring speed is 100 rpm-500 rpm, and in this embodiment, preferably 400 rpm-450 rpm; the stirring time and UV irradiation time are 5-15 min; the mixing and emulsification device for the oil phase and the aqueous phase can adopt a mechanical stirring, magnetic stirring or homogenizing stirring device, and in this embodiment, a homogenizing stirring device is preferred.

[0092] 2. Mineralization of SilMA hydrogel microspheres

[0093] The harvested SilMA hydrogel microspheres were immersed in a calcium chloride / phosphoric acid mixed solution with a calcium chloride / phosphoric acid molar ratio of 1.67. After soaking for 24 hours, the solution was filtered and the upper mineralized liquid was discarded. Subsequently, a 15% (W / V) ammonia solution was added. After reacting for 3 hours, the supernatant solution was filtered and discarded, and the prepared mineralized SilMA hydrogel microspheres were washed with water multiple times.

[0094] The molar ratio of the calcium chloride / phosphoric acid mixed solution is 1.5-2.0, preferably 1.5-1.7 in this embodiment; the immersion time in the mineralizing solution is 12 hours to 48 hours, preferably 24 hours in this embodiment; the volume fraction of the ammonia solution is 10% to 20%, preferably 15% in this embodiment; and the ammonia solution action time is 30 minutes to 2 hours.

[0095] 3. Critical Point Drying of Mineralized SilMA Hydrogel Microspheres

[0096] The mineralized SilMA hydrogel microspheres were dehydrated using a gradient ethanol-water solution with a concentration of 30%-50%-70%-90%-100%; the soaking time for each ethanol concentration was 15 minutes; then critical point drying was performed in a critical point dryer for 3 hours to harvest dry mesoporous mineralized silk fibroin methacrylamide microspheres (mSilMA for short).

[0097] The microspheres are immersed in the ethanol aqueous solution for 15-30 minutes; the critical point drying time is 1-5 hours, preferably 3-5 hours in this embodiment.

[0098] 4. Calculation of BMP-2 content bound to mSilMA microspheres

[0099] Weigh 10 mg of mSilMA prepared in Step 3 and add 500 ng of bone morphogenetic protein (BMP-2) solution. After incubation at 4°C for 24 hours, wash the microspheres three times with 5 mL of saline (containing 0.1% bovine serum albumin) to remove any unbound BMP-2. The wash solution was collected from each of the three washes and assayed for BMP-2 content using an enzyme-linked immunosorbent assay (ELISA). The BMP-2 content per milligram of microspheres was calculated as: (initial BMP-2 amount added minus the BMP-2 content in the wash solution) / total mass of microspheres.

[0100] 5. In vitro sustained release assay of BMP-2

[0101] 10 mg of 20% mSilMA microspheres and 10 mg of 20% SilMA microspheres were weighed, and 500 μl of a 500 ng BMP-2 solution (solvent: saline containing 0.1% bovine serum albumin) was added to each microsphere. The microspheres were incubated at 4°C for 24 hours. Then, 5 mL of saline containing 0.1% bovine serum albumin was added to each microsphere and washed three times at room temperature. For each microsphere, 15 mL of wash solution was collected. Unbound BMP-2 in the wash solution was assayed using a BMP-2 enzyme-linked immunosorbent assay kit; the bound BMP-2 content was equal to the original amount added (500 ng) minus the BMP-2 content in the wash solution.

[0102] 20% mSilMA microspheres and 20% SilMA microspheres bound to BMP-2 were immersed in 5 mL of saline containing 0.1% bovine serum albumin and incubated at 37°C. Supernatants were collected on days 1, 4, 7, 124, 21, 28, and 35, and BMP-2 levels were measured using a BMP-2 enzyme-linked immunosorbent assay (ELISA) kit. The percentage of BMP-2 released at a specific time was calculated as: cumulative amount of BMP-2 released in the supernatant during that time period divided by the total amount of BMP-2 bound to the microspheres; the cumulative percentage of BMP-2 released was calculated as: the sum of all percentages of BMP-2 released during that time period.

[0103] In summary, the preparation process of dry mesoporous mineralized silk methacrylamide microspheres (mSilMA) is as follows: Figure 1 The prepared mSilMA has a particle size of 100-500 μm, preferably 250-350 μm in this embodiment; the surface of the mSilMA has an interconnected fiber network structure and needle-shaped calcium phosphate material, and the pore size of the fiber network is 5-100 nm, preferably 10-15 nm in this embodiment.

[0104] Therefore, by adopting the optimal preparation method of the present invention, based on the silk fibroin material with good biocompatibility, coupling the biomimetic mineralization method and the critical point drying method, the long-term low-amount release of BMP-2 in vitro was achieved without the occurrence of early burst release.

[0105] Example 2 Screening of the main components of microspheres and the necessity of "mesopore channel" structure in microspheres

[0106] In order to obtain the microspheres with the best performance in Example 1 that can release bone morphogenetic protein in a long-term, low-dose sustained manner, the main components of the microspheres were first screened in this example. The specific screening process is as follows (the remaining operating procedures and experimental conditions not mentioned are the optimal conditions in Example 1):

[0107] 1. Comparison of results under scanning electron microscope

[0108] The main components of the microspheres are silk methacrylamide and gelatin methacrylamide, respectively, to prepare gelatin methacrylamide hydrogel microspheres (abbreviated as GelMA) and silk fibroin methacrylamide microspheres (SilMA), respectively. The specific preparation process is as follows:

[0109] Gelatin methacrylamide (GelMA) and silk fibroin methacrylamide (SilMA) hydrogel microspheres of equal concentrations were prepared using a UV-crosslinked oil / water emulsion method. Simultaneously, the hydrogel microspheres were dehydrated by immersing them in a gradient of ethanol solutions ranging from 30% to 50% to 70% to 90% to 100% for 15 minutes at each ethanol concentration. Subsequently, the hydrogel microspheres were critically dried for 3 hours using a critical point dryer, and the dried GelMA and SilMA microspheres were harvested.

[0110] Specific results such as Figure 2 As shown, Figure 2 The surface morphologies of GelMA and SilMA microspheres after critical point drying, as observed by scanning electron microscopy (SEM). Scanning electron microscopy revealed that after the same ethanol gradient dehydration and critical point drying, the GelMA hydrogel microspheres exhibited a non-porous structure, rather than a surface-penetrating mesoporous structure. In contrast, the SilMA microspheres exhibited interconnected pores. This suggests that not all materials can form pores through critical point drying.

[0111] In the critical point drying method, the medium undergoes a phase transition from liquid carbon dioxide to supercritical carbon dioxide to gaseous carbon dioxide, reducing the surface stress at the interface to zero and preserving the sample's fine structure. Silk fibroin is a naturally occurring high-molecular-weight fibrous protein extracted from silk and possesses a fibrous structure. Gelatin, on the other hand, is a type of protein derived from the partial hydrolysis of collagen fibers. Collagen possesses a rod-shaped triple helical structure. During the partial hydrolysis process to produce gelatin, this triple helical structure separates and breaks, resulting in the loss of the gelatin's fibrous structure. It is speculated that critical point drying is able to recreate the original fibrous structure of silk fibroin, precisely because it possesses this original fibrous structure. However, gelatin itself lacks a well-defined fibrous structure. Furthermore, during ethanol gradient dehydration, the hydrogel's inherent network structure gradually densifies as water is lost. Consequently, critical point drying eliminates this fibrous network, resulting in a dense, non-porous surface. Therefore, it is speculated that if a material possesses an inherent fibrous structure, critical point drying can produce a porous structure; however, if a material lacks this inherent fibrous structure, critical point drying cannot.

[0112] In the present invention, the mesoporous channel structure is crucial for preparing hydrogel microspheres that can release BMP-2 in a long-term, low-volume sustained manner. First, the presence of mesopores can significantly increase the drug loading capacity; second, the interconnected mesoporous channels are extremely advantageous. The structure is conducive to the diffusion and release of cell active factors within the microspheres, enabling the slow and sustained release of cell active factors, avoiding the sudden release of cell active factors, thereby extending the action time of cell active factors in the body, improving the utilization efficiency and therapeutic effect of cell active factors, and providing long-lasting and stable support for processes such as bone repair; on the other hand, the mesoporous structure plays a key role in the material exchange and information transmission between the microspheres and the surrounding environment, enhancing the interaction between the microspheres and the body, and improving the adaptability and biocompatibility of the microspheres in the body.

[0113] Therefore, in this embodiment, silk fibroin methacrylamide, which can form a mesoporous structure, is preferably used as the main component of the microspheres to achieve more ideal drug controlled release effect and biological application performance, providing strong technical support and innovative ideas for the development of fields such as bone tissue engineering.

[0114] 2. Comparison of BMP-2 protein loading rate and long-term low-dose sustained-release capacity

[0115] 1. Comparison of BMP-2 protein loading rate

[0116] To further demonstrate the importance of using silk fibroin in the successful preparation of mSilMA, a material with high protein loading and long-term, low-volume sustained release of bone morphogenetic protein, the gelatin methacrylamide hydrogel microspheres (GelMA) and silk fibroin methacrylamide microspheres (SilMA) from Step 1 were used in this example, and the optimal preparation method described in Example 1 was used to prepare GelMA and mSilMA microspheres. 10 mg of each was weighed, and 500 μl of a 500 ng BMP-2 solution (solvent: saline containing 0.1% bovine serum albumin) was added to each microsphere. The microspheres were incubated at 4°C for 24 hours, and then 5 mL of saline containing 0.1% bovine serum albumin was added to each microsphere. The microspheres were washed three times at room temperature. 15 mL of washing solution was collected from each microsphere. Unbound BMP-2 in the washing solution was detected using a BMP-2 enzyme-linked immunosorbent assay kit (purchased from Shenzhen Xinbosheng Biotechnology Co., Ltd., model number: EHC172.96). The amount of BMP-2 bound per milligram of microspheres was calculated as (the original amount added (500 ng) minus the amount of BMP-2 in the wash solution) / total mass of microspheres. The specific amounts of BMP-2 bound by different microspheres are shown in Table 1.

[0117] 2. Comparison of the long-term, low-dose sustained-release capacity of BMP-2

[0118] As above, GelMA microspheres and mSilMA microspheres bound to BMP-2 were immersed in 5 mL of saline containing 0.1% bovine serum albumin and incubated at 37°C. Supernatants were collected at 1, 4, 7, 14, 21, 28, and 35 days, and the BMP-2 content in the supernatants was assayed using a BMP-2 enzyme-linked immunosorbent assay kit. The percentage of BMP-2 released at a specific time was calculated as: cumulative BMP-2 released in the supernatant over the specified time period / total BMP-2 bound to the microspheres (%). The in vitro BMP-2 release capacity of different microspheres over a specific time period is shown in Table 2.

[0119] 3. Experimental results

[0120] The results of the above different experiments are shown in Tables 1 and 2:

[0121] Table 1. Content of BMP-2 bound to different microspheres

[0122]

[0123] Table 2. BMP-2 release capacity in vitro of different microspheres within a certain period of time

[0124]

[0125] As shown in Tables 1 and 2, only when silk methacrylamide was used as the main component, SilMA microspheres with a surface-penetrating mesoporous structure were successfully prepared. The BMP-2 protein loading rate reached 88.68%, while also enabling sustained, low-dose sustained release of BMP-2, with a cumulative release of approximately 2.5% over four weeks in vitro. Using other components failed to achieve the same effects as described in the present invention. Therefore, in this example, silk methacrylamide, which can form mesopores, was preferred as the main component of the microspheres.

[0126] Example 3 Screening of different drying methods for preparing dry SilMA

[0127] To obtain the mSilMA with the best performance in Example 1, the drying method of the mineralized SilMA hydrogel microspheres during the preparation of mSilMA was screened in this example. The specific screening process is as follows (the remaining operating procedures and experimental conditions not mentioned are the optimal conditions in Example 1):

[0128] 1. Comparison of results under scanning electron microscope

[0129] The prepared mineralized SilMA hydrogel microspheres were dehydrated by freeze drying and critical point drying, respectively, and the obtained dry SilMA microspheres were observed by scanning electron microscopy.

[0130] 1. Freeze drying: The prepared mineralized SilMA hydrogel microspheres were directly pre-frozen in a -80°C refrigerator for 24 h, and then dried using a freeze dryer. Dry non-porous SilMA microspheres were harvested after 48 h.

[0131] 2. Critical point drying: The prepared mineralized SilMA hydrogel microspheres were immersed in a 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, with the immersion time at each ethanol concentration being 15 minutes; then, critical point drying was performed using a critical point dryer for 3 hours to harvest dry mesoporous mineralized silk fibroin methacrylamide microspheres (mSilMA).

[0132] Specific results such as Figure 3 As shown, Figure 3 The surface morphology of dry SilMA microspheres prepared by freeze drying and critical point drying methods is shown. Figure 3 It can be seen that the mSilMA microspheres prepared by the critical point drying method have a smooth and uniform surface, no adhesion phenomenon, and the surface of the microspheres has uniformly distributed mesopores; the uniform mesoporous structure is conducive to the loading and sustained release of drugs, and can provide a more stable and controllable release environment for drugs such as BMP-2, thereby better exerting the role of the drugs and improving the therapeutic effect.

[0133] However, the dry SilMA microspheres prepared by freeze-drying method not only fail to form mesopores on the surface of the microspheres, resulting in limited drug loading and sustained-release performance, but also cause adhesion between the microspheres, resulting in a rough surface. This rough surface and adhesion phenomenon may affect the dispersibility and stability of the microspheres, and thus affect their effectiveness in practical applications.

[0134] 2. Comparison of BMP-2 protein loading rate and long-term low-dose sustained-release capacity

[0135] 1. Comparison of BMP-2 protein loading rate

[0136] At the same time, in order to further verify the importance of using a drying method (critical drying method) in the successful preparation of mSilMA with high protein loading rate and long-term low-dose sustained release of bone morphogenetic protein, in this example, the following 10 mg of microspheres were weighed:

[0137] 1. Dry non-porous mineralized SilMA microspheres prepared by freeze drying in step 1;

[0138] 2. Dry mesoporous mineralized SilMA microspheres prepared by critical point drying (mSilMA microspheres prepared by the best preparation method in Example 1);

[0139] 3. and undried mineralized SilMA hydrogel microspheres (the microspheres were prepared by the same method as in Example 1, except for the drying step);

[0140] 500 μl of a 500 ng BMP-2 solution (solvent: saline containing 0.1% bovine serum albumin) was added to each microsphere and incubated at 4°C for 24 hours. Then, 5 mL of saline containing 0.1% bovine serum albumin was added to each microsphere and washed three times at room temperature. For dry nonporous mineralized SilMA microspheres, dry mesoporous mineralized SilMA microspheres, and mineralized SilMA hydrogel microspheres, 15 mL of washing solution was used. Unbound BMP-2 in the washing solution was detected using a BMP-2 enzyme-linked immunosorbent assay kit. The amount of BMP-2 bound per milligram of microspheres was calculated as: (original amount added (500 ng) minus the amount of BMP-2 in the washing solution) / total mass of microspheres. The amount of BMP-2 bound to different microspheres is shown in Table 3.

[0141] 2. Comparison of the long-term, low-dose sustained-release capacity of BMP-2

[0142] As described above, dry, non-porous SilMA microspheres and mSilMA microspheres bound to BMP-2 were immersed in 5 mL of saline containing 0.1% bovine serum albumin and incubated at 37°C. Supernatants were collected at 1, 4, 7, 14, 21, 28, and 35 days, and the BMP-2 content in the supernatants was assayed using a BMP-2 enzyme-linked immunosorbent assay kit. The percentage of BMP-2 released at a specific time was calculated as: cumulative amount of BMP-2 released in the supernatant over the specified time period / total amount of BMP-2 bound to the microspheres (%). The in vitro BMP-2 release capacity of different microspheres over a specific time period is shown in Table 4.

[0143] 3. Experimental results

[0144] The results of the above different experiments are shown in Tables 3 and 4:

[0145] Table 3. Content of BMP-2 bound to different microspheres

[0146]

[0147] Table 4. BMP-2 release capacity in vitro of different microspheres within a certain period of time

[0148]

[0149] As can be seen from Tables 3 and 4, only when the critical point drying method is used can SilMA microspheres with a surface-through mesoporous structure be successfully prepared, with a BMP-2 protein loading rate of 88.68% and a continuous low-amount sustained release of BMP-2, with a cumulative release of about 2.51% of BMP-2 over 4 weeks in vitro. When other drying methods or no drying are used, the effects of the present invention cannot be achieved, the BMP-2 protein loading rate is significantly reduced, and the in vitro controlled release ability of BMP-2 is also significantly reduced. Therefore, in this embodiment, the critical point drying method is preferably used to prepare mSilMA.

[0150] Example 4 Screening of different mineralization methods in the preparation of mineralized SilMA hydrogel microspheres

[0151] In order to obtain the mSilMA with the best performance in Example 1, different mineralization methods were screened during the preparation of mineralized SilMA hydrogel microspheres in this example. The specific screening process is as follows (the remaining operating procedures and experimental conditions not mentioned are the optimal conditions in Example 1):

[0152] 1. 10x Simulated Body Fluid (SBF): Simulated body fluid (SBF) is the most commonly used solution for in vitro simulation and forms the basis for in vitro simulation experiments. Designed based on the ion concentration of human plasma, SBF is used to test the bioactivity of materials. The principle of SBF is that, after implantation, synthetic materials can form a bone-like apatite layer on their surface, thereby bonding to bone. Similarly, if synthetic materials can form hydroxyapatite in SBF, which has an ion concentration similar to human plasma, this indicates that the material is bioactive.

[0153] Prepare 500 mL of 10x simulated body fluid: sodium chloride 1000 mmol / L, potassium chloride 5 mmol / L, calcium chloride dihydrate 25 mmol / L, magnesium chloride hexahydrate 5 mmol / L, sodium dihydrogen phosphate 10 mmol / L, pH = 7.2-7.4.

[0154] 2. Nanocluster method (PILP): Weigh 2.15g of polyacrylic acid (PAA), 1.08g of polyaspartic acid (PASP), and 0.362g of disodium hydrogen phosphate into a 100mL beaker. Add 25mL of ultrapure water. Place a rotor in the beaker, seal with tin foil, and stir overnight at room temperature. A dark yellow viscous solution A is obtained.

[0155] Weigh 3 g of PASP, add 10 mL of double-distilled water, and dissolve and mix thoroughly.

[0156] Under magnetic stirring, add 0.1 mL of PASP solution to a beaker. Slowly add 2 mL of 0.1 mol / L CaCl2 solution dropwise. Then, slowly add 2 mL of Solution A dropwise using a syringe and stir thoroughly. Slowly add 0.4 mL of 3 mol / L NaOH solution dropwise and stir thoroughly to mix. The resulting nanoclusters can be stored at 4°C for 2 weeks.

[0157] 3. Calcium chloride / phosphoric acid-ammonia reaction method (Ca / P method): prepare 500 mL of 1x calcium chloride / phosphoric acid solution with a calcium chloride / phosphoric acid molar ratio of 1.67, a calcium chloride concentration of 0.167 mol / L, a phosphoric acid concentration of 0.1 mom / L, and an ammonia volume fraction of 15% (V / V).

[0158] Equal amounts of SilMA microspheres were immersed in the above three mineralization solutions for 24 hours. For the 10×SBF method and the PILP method, after immersion for 24 hours, the microspheres were washed with water three times, and the microspheres were directly collected, dehydrated with ethanol gradient, and then critically dried. For the Ca / P method, after immersion for 24 hours, the microspheres were filtered and the upper mineralization solution was discarded. Subsequently, 15% (W / V) ammonia solution was added, and after reaction for 3 hours, the supernatant was filtered and discarded. The prepared mineralized microspheres were then washed with water three times, dehydrated with ethanol gradient, and then critically dried.

[0159] Specific results such as Figure 4 As shown, Figure 4 The structure and content of calcium phosphate formed on the surface of SilMA microspheres by different mineralization methods are shown. Figure 4 It can be seen that the Ca / P method can form a more uniform and denser calcium phosphate mineralized coating on the surface of SilMA microspheres, and a more uniform and denser calcium phosphate mineralized coating can enhance the stability and mechanical strength of the microspheres, improve the compatibility and binding ability of the microspheres with bone tissue, and help to better promote bone regeneration and repair processes; In addition, the uniform and high-density coating can more effectively control the release rate of the drug, provide a more stable loading environment for the drug, and thus improve the therapeutic effect of the drug. Therefore, in this embodiment, the Ca / P method is preferred as the mineralization method of SilMA microspheres.

[0160] Example 5 Screening of different mineralization concentrations in the preparation of mineralized SilMA hydrogel microspheres

[0161] To obtain the optimal mSilMA performance described in Example 1, this example screened different mineralization concentrations during the preparation of mineralized SilMA hydrogel microspheres using the Ca / P method, and investigated their effects on the SilMA microspheres and the surface calcium-phosphate mineralization layer. The specific screening process is as follows (all other procedures and experimental conditions not mentioned are those optimized in Example 1):

[0162] First, the different mineralization concentrations in the Ca / P method are defined as follows:

[0163] 1x Ca / P mineralization solution: calcium chloride / phosphoric acid molar ratio is 1.67, calcium chloride concentration is 0.167 mol / L, phosphoric acid concentration is 0.1 mom / L;

[0164] 5x Ca / P mineralization solution means that the concentrations of calcium chloride and phosphoric acid are increased by 5 times at the same time: the concentration of calcium chloride is 0.835mol / L, and the concentration of phosphoric acid is 0.5mom / L;

[0165] 10x Ca / P mineralization solution means that the concentrations of calcium chloride and phosphoric acid are increased 10 times at the same time: the concentration of calcium chloride is 1.67mol / L, and the concentration of phosphoric acid is 1.0mom / L;

[0166] The same mineralization steps were used for mineralization and subsequent critical point drying: 20% SilMA microspheres were immersed in the above three mineralization solutions for 24 hours, filtered, and the upper mineralization solution was discarded; then 15% (W / V) ammonia solution was added, reacted for 3 hours, and the supernatant was filtered and discarded. The prepared mineralized microspheres were then washed with water three times, dehydrated with ethanol gradient, and then critical point dried.

[0167] Specific results such as Figure 5 As shown, Figure 5 The effects of three concentrations of Ca / P mineralization solution on the structure and surface mineralization coating of 20% SilMA microspheres are shown. It can be seen that when other conditions remain unchanged, increasing the concentration of the Ca / P mineralization solution will lead to the destruction of the microsphere structure, while the calcium-phosphorus coating still maintains a needle-like structure. As the concentration of the Ca / P mineralization solution increases, the coating density increases. Because 5-fold and 10-fold Ca / P mineralization solutions significantly damage the microsphere structure, the preferred 1-fold calcium-phosphorus mineralization solution in this embodiment retains the intact structure of the microspheres at this concentration. A relatively evenly distributed needle-like calcium-phosphorus coating can be present on the surface of the 20% SilMA microspheres, while the mesoporous channels of the microspheres themselves are not completely blocked by the needle-like calcium-phosphorus coating.

[0168] At the same time, based on the 1x Ca / P mineralization method, this example also conducted nitrogen physical adsorption tests on the prepared dry mesoporous 20% SilMA microspheres (abbreviated as 20% SilMA) and dry mesoporous mineralized 20% SilMA microspheres (abbreviated as 20% mSilMA) to compare the pore size distribution of the two, thereby further understanding the effect of mineralization treatment on the pore size of the microspheres and evaluating the changes in the physical properties of the microspheres during the mineralization process. The specific results are as follows: Figure 6 A in Figure 6 B and Figure 6 As shown in C, from Figure 6 B and Figure 6In Figure C, we can see that the average pore size of the surface of 20% mSilMA microspheres is about 10nm, while the average pore size of 20% SilMA is about 19nm (as shown in the figure). Figure 6 A and Figure 6 As shown in C in the figure). Therefore, it can be seen that the 1x Ca / P mineralization solution concentration is more appropriate, and the mineralization treatment will reduce the pore size of the microspheres. Within the appropriate range, the pore size of the microsphere surface is smaller, which has the following advantages: (1) Better controlled release performance: smaller pore size can more effectively control the release rate and amount of drugs or bioactive molecules, enabling them to be released continuously and stably for a longer period of time, thereby improving the therapeutic effect; (2) Enhanced stability: smaller pore size may make the microsphere structure more stable, reduce the impact of the external environment on the internal loaded substances, and improve the stability of the microspheres during storage and use; (3) Improved selectivity: It can more selectively allow molecules of a specific size to pass through or be adsorbed, thereby achieving more accurate delivery of drugs or bioactive molecules; (4) Reduced burst release: Reduced sudden and large-scale release of drugs or bioactive molecules in the initial stage, making the release of drugs or bioactive molecules more uniform and controllable.

[0169] Therefore, it can be seen that in the present invention, mineralization treatment is an indispensable step. Only by mineralizing the dry mesoporous SilMA microspheres and adopting the mineralization method and the 1-fold Ca / P mineralization method can mSilMA with a complete structure and a uniform mineralized coating be prepared, achieving the best effect of optimizing the physical properties of the microspheres and the controlled release performance of BMP-2, providing a more ideal material choice for applications in related fields such as bone repair.

[0170] Example 6 Necessity of the Mineralization Step for the In Vitro Controlled Release of BMP-2 from the mSilMA of the Present Invention

[0171] In this example, the surface morphologies of 20% mSilMA microspheres (dry mesoporous mineralized microspheres) and 20% SilMA microspheres (dry mesoporous microspheres) prepared by the 1x Ca / P mineralization method were further compared, and the characteristic elements of the mineralized coating on the surface of 20% mSilMA microspheres were detected and verified. Figure 7 As shown in A.

[0172] At the same time, in order to verify the necessity of mineralization for the preparation of mSilMA in the present invention, the following microspheres were also taken in this example:

[0173] 1. 20% mSilMA microspheres (microspheres prepared using the optimal preparation method in Example 1);

[0174] 2. 20% SilMA microspheres (the dry mesopores were not mineralized, and the remaining steps were the same as the optimal preparation method in Example 1);

[0175] 3. Using other mineralization methods: microspheres prepared by the 10-fold simulated body fluid method in Example 4;

[0176] 4. Using other mineralization methods: microspheres prepared by the nanocluster method in Example 4;

[0177] 5. Microspheres prepared using other mineralization concentrations: 5 times the Ca / P mineralization solution in Example 5;

[0178] 6. Microspheres prepared using other mineralization concentrations: 10 times the Ca / P mineralization solution in Example 5;

[0179] The differences in the in vitro controlled release ability of BMP-2 of the microspheres prepared by the above-mentioned different methods were compared and tested. The steps for the in vitro release test of BMP-2 are as follows:

[0180] (1) Comparison of BMP-2 protein loading rate: Weigh each of the above-mentioned different microspheres, add 500 μl of 500 ng BMP-2 solution (solvent is saline containing 0.1% bovine serum albumin), incubate at 4°C for 24 h, then add 5 mL of saline containing 0.1% bovine serum albumin, and wash three times at room temperature. 15 mL of washing solution can be collected for each of the above-mentioned 6 different microspheres. The BMP-2 enzyme-linked immunosorbent assay kit is used to detect the BMP-2 not bound by the microspheres in the washing solution. The bound BMP-2 is equal to the original amount added (500 ng) minus the BMP-2 content in the washing solution.

[0181] (2) Comparison of the long-term, low-volume sustained-release capacity of BMP-2: The above-mentioned microspheres, each of which was bound to BMP-2, were immersed in 5 mL of physiological saline containing 0.1% bovine serum albumin and incubated at 37°C. The supernatant was collected on days 1, 4, 7, 14, 21, 28, and 35, and the BMP-2 content in the supernatant was detected using a BMP-2 enzyme-linked immunosorbent assay kit. The percentage of BMP-2 released at a specific time was calculated as: the cumulative amount of BMP-2 released in the supernatant during the time period / the total amount of BMP-2 bound to the microspheres.

[0182] The results of the above different experiments are shown in Tables 5, 6 and Figure 7 As shown in B:

[0183] Table 5. Content of BMP-2 bound to different microspheres

[0184]

[0185] Table 6. BMP-2 release capacity in vitro of different microspheres within a certain period of time

[0186]

[0187] It can be seen from Tables 5 and 6 that only when the Ca / P method is used as the mineralization method and the mineralization concentration is 1 times the Ca / P mineralization solution, can complete mSilMA microspheres with a surface-through mesoporous channel structure be successfully prepared, and the BMP-2 protein loading rate can reach 88.68%. At the same time, BMP-2 can be continuously released in low amounts, with a cumulative release of about 2.5% of BMP-2 in vitro for 4 weeks; when other mineralization methods, mineralization concentrations or no mineralization treatment is used, the effects of the present invention cannot be achieved, the BMP-2 protein loading rate is significantly reduced, and the in vitro controlled release ability of BMP-2 is also significantly reduced.

[0188] At the same time, from Figure 7 It can also be seen from Figure B that the in vitro BMP-2 sustained-release test found that 20% mSilMA microspheres could sustain low-amount sustained-release of BMP-2, with a cumulative release of about 2% of BMP-2 in vitro after 4 weeks, while 20% SilMA microspheres failed to release BMP-2 for a long time, but reached a plateau in about 3 weeks. This may be because the adsorption / dissolution of the drug by the mesopores reached a certain equilibrium, resulting in incomplete release.

[0189] Therefore, in this embodiment, the critical point drying method is preferably used to prepare mSilMA.

[0190] Example 6 Screening of different SilMA solution concentrations during the preparation of SilMA

[0191] To obtain the mSilMA with the best performance in Example 1, the concentration of the SilMA solution was screened during the preparation of SilMA in this example. The specific screening process is as follows (the remaining operating procedures and experimental conditions not mentioned are the optimal conditions in Example 1):

[0192] 1. Preparation of microspheres with different concentrations

[0193] 1. The concentration of SilMA solution is 10% (W / V%)

[0194] SilMA was dissolved in double-distilled water at 25°C to obtain a 10% (w / v%) SilMA solution. A specific volume of LAP solution was added as the aqueous phase to a final concentration of 0.25% (w / v%). The oil phase consisted of liquid paraffin and Span 80 in a 1:20 ratio. The aqueous phase was added dropwise to the oil phase at a 5:1 oil / water ratio. The mixture was stirred at 400 rpm at 25°C and irradiated with UV light during stirring. After 10 minutes, stirring and irradiation were stopped, and the mixture was allowed to settle to the bottom of the beaker. The supernatant (oil phase) was discarded and the mixture was washed three times with 50% isopropanol, twice with 75% isopropanol, and once with 80% isopropanol. The mixture was then washed three times with copious amounts of water. The mixture was allowed to settle to the bottom of the beaker. The supernatant (water) was discarded and the microspheres were harvested by filtration. The 10% SilMA hydrogel microspheres were immersed in 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, with the soaking time at each ethanol concentration being 15 minutes; then critical point drying was performed in a critical point dryer for 3 hours to harvest 10% dry mesoporous silk fibroin methacrylamide microspheres (abbreviated as 10% SilMA).

[0195] 2. The concentration of SilMA solution is 20% (W / V%)

[0196] SilMA was dissolved in double-distilled water at 25°C to obtain a 20% (w / v%) SilMA solution. A specific volume of LAP solution was added as the aqueous phase to a final concentration of 0.25% (w / v%). The oil phase consisted of liquid paraffin and Span 80 in a 1:20 ratio. The aqueous phase was added dropwise to the oil phase at a 5:1 oil / water ratio. The mixture was stirred at 400 rpm at 25°C and irradiated with UV light during stirring. After 10 minutes, stirring and irradiation were stopped, and the mixture was allowed to settle to the bottom of the beaker. The supernatant (oil phase) was discarded, and the mixture was washed three times with 50% isopropanol, twice with 75% isopropanol, and once with 80% isopropanol. The mixture was then washed three times with copious amounts of water. The mixture was allowed to settle to the bottom of the beaker. The supernatant (water) was discarded and the microspheres were harvested by filtration. The 20% SilMA hydrogel microspheres were immersed in 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, with the soaking time at each ethanol concentration being 15 minutes; then critical point drying was performed in a critical point dryer for 3 hours to harvest 20% dry mesoporous silk fibroin methacrylamide microspheres (abbreviated as 20% SilMA).

[0197] 3. The concentration of SilMA solution is 30% (W / V%)

[0198] SilMA was dissolved in double-distilled water at 25°C to obtain a 30% (w / v%) SilMA solution. A specific volume of LAP solution was added as the aqueous phase to a final concentration of 0.25% (w / v%). The oil phase consisted of liquid paraffin and Span 80 in a 1:20 ratio. The aqueous phase was added dropwise to the oil phase at a 5:1 oil / water ratio. The mixture was stirred at 400 rpm at 25°C and irradiated with UV light during stirring. After 10 minutes, stirring and irradiation were stopped, and the mixture was allowed to settle at the bottom of the beaker. The supernatant (oil phase) was discarded, and the mixture was washed three times with 50% isopropanol, twice with 75% isopropanol, and once with 80% isopropanol. The mixture was then washed three times with copious amounts of water. The mixture was allowed to settle at the bottom of the beaker. The supernatant (water) was discarded and the microspheres were harvested by filtration. The 30% SilMA hydrogel microspheres were immersed in 30%-50%-70%-90%-100% ethanol aqueous solution for gradient dehydration, with the soaking time at each ethanol concentration being 15 minutes; then critical point drying was performed in a critical point dryer for 3 hours to harvest 30% dry mesoporous silk fibroin methacrylamide microspheres (abbreviated as 30% SilMA).

[0199] 2. Results Analysis

[0200] The swelling properties and surface pore size of the dry mesoporous silk fibroin methacrylamide microspheres prepared using SilMA solutions of different concentrations were statistically analyzed. The specific results are as follows:

[0201] 1. Swelling performance test

[0202] Identical masses of 10%, 20%, and 30% dry mesoporous SilMA microspheres were weighed and immersed in equal volumes of phosphate buffer for 48 hours. The supernatant was filtered, the microspheres harvested, and weighed. The swelling properties of the mesoporous SilMA microspheres at different concentrations were preliminarily defined by the percentage increase in mass at each concentration.

[0203] Figure 8 A in the figure is the swelling performance result of 10%, 20%, and 30% SilMA microspheres. Figure 8 As shown in Figure A, the 10% SilMA microspheres have the strongest water absorption and swelling ability, and are easily swollen and broken within 1 week of immersion, losing their structural integrity, which indicates that they are not stable enough and are not suitable for subsequent treatments; while there is no obvious difference in the water absorption and swelling ability of the 20% and 30% SilMA microspheres.

[0204] 2. Statistical analysis of surface pore size

[0205] Based on the surface structure scanning electron microscopy images of mesoporous SilMA microspheres with different concentrations, the surface pore diameters of mesoporous SilMA microspheres at each concentration were measured and counted using ImageJ software, and statistical analysis was performed using GraphPad Prism software.

[0206] Figure 9 The SEM results of 10%, 20% and 30% mesoporous SilMA microspheres are shown in Figure 2. Figure 8 The result shown in B is from Figure 8 As shown in Figure B, the 10% SilMA microspheres have the largest surface pore size, with an average pore size of approximately 100 nm. The 20% SilMA microspheres have a surface pore size of approximately 20 nm, and the 30% SilMA microspheres have an average surface pore size of approximately 5 nm. Since the molecular diameter of bone morphogenetic protein is approximately 10 nm, only the 20% SilMA microspheres, with a surface pore size of approximately 20 nm, can accommodate the entry of bone morphogenetic protein while limiting its rapid release to a certain extent, thus achieving a better controlled release effect. The 30% SilMA microspheres, however, have an average surface pore size of approximately 5 nm. For bone morphogenetic protein, which has a molecular diameter of approximately 10 nm, the pore size is too small, which is not conducive to the effective loading and subsequent release of bone morphogenetic protein.

[0207] Therefore, considering the swelling properties and surface pore size distribution of SilMA microspheres with different concentrations, 20% SilMA microspheres performed more balanced and ideal in terms of stability, bone morphogenetic protein loading and controlled release. Therefore, 20% SilMA microspheres were preferred for the next step of biomimetic mineralization.

[0208] Example 7 Screening of different preparation methods for preparing SilMA

[0209] In order to obtain the mSilMA with the best performance in Example 1, different preparation methods were screened during the preparation of SilMA in this example. The specific screening process is as follows (the remaining operating procedures and experimental conditions not mentioned are the optimal conditions in Example 1):

[0210] 1. UV cross-linking oil / water emulsification method (mechanical stirring): the specific preparation steps are as shown in Example 1;

[0211] 2. Photo-crosslinking 3D printing technology: SilMA is prepared using photo-crosslinking 3D printing technology;

[0212] The specific results of SilMA obtained by different preparation methods are as follows Figure 10 A and Figure 10 As shown in B, Figure 10 A in the figure is a light microscopy image of 20% SilMA hydrogel microspheres prepared by the photocrosslinking oil / water emulsification method (mechanical stirring); Figure 10 B in the figure is a light microscopy image of 20% SilMA hydrogel microspheres prepared by photo-crosslinking 3D printing technology. Figure 10It can be seen that SilMA prepared by the UV-crosslinked oil / water emulsification method (mechanical stirring) of the present invention has significant advantages in terms of yield and sphericity compared to microspheres prepared by photo-crosslinked 3D printing technology; microspheres prepared by photo-crosslinked 3D printing technology are prone to adhesion and have poor sphericity, and are mostly cylindrical.

[0213] In addition, the mechanical stirring method used in the present invention can change parameters such as the oil / water ratio and stirring speed, thereby successfully preparing microspheres with a particle size range of 1μm-1000μm. However, the photo-cross-linking 3D printing technology cannot print and form microspheres below 100μm, and can only print microspheres of specific sizes, such as 200μm, 400μm, etc. In addition, the number of printed microspheres is limited by the volume of the printing ink and the size of the printable stage.

[0214] Therefore, in this embodiment, the UV-crosslinked oil / water emulsification method (mechanical stirring) is preferably used to prepare SilMA, which has the best performance in terms of yield, sphericity, and controllable particle size range, can better meet the needs of practical applications, and lays a solid foundation for the subsequent preparation of mSilMA with excellent performance.

[0215] Although the present invention has been disclosed above in terms of preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing ready-to-use mesoporous mineralized silk fibroin microspheres, characterized in that: The following steps are involved: (1) Preparation of SilMA hydrogel microspheres; (2) Mineralizing SilMA hydrogel microspheres; (3) drying the mineralized SilMA hydrogel microspheres to obtain dry mesoporous mineralized SilMA microspheres; In the step (1), SilMA hydrogel microspheres are prepared by ultraviolet cross-linking oil / water emulsification method and mechanical stirring; in the step (2), Ca / P method is used for mineralization; and in the step (3), critical point drying method is used for drying.

2. The preparation method according to claim 1, characterized in that The mineralization concentration is 1 times Ca / P mineralization solution, and in the 1 times Ca / P mineralization solution, the molar ratio of calcium chloride to phosphoric acid is 1.5-2.

0.

3. The preparation method according to claim 2, characterized in that: The SilMA hydrogel microspheres are immersed in a calcium chloride / phosphoric acid mixed solution, filtered after immersion, the upper mineralized liquid is discarded, and then an ammonia solution is added, reacted, filtered and the supernatant solution is discarded, and the prepared mineralized SilMA hydrogel microspheres are washed with water multiple times; wherein the immersion time is 12 hours to 48 hours; the volume fraction of the ammonia solution is 10% to 20%, and the ammonia action time is 30 minutes to 2 hours.

4. The preparation method according to claim 3, characterized in that: In the step (1), SilMA is first dissolved in double distilled water to obtain a SilMA solution, a LAP solution is added to the SilMA solution as an aqueous phase, liquid paraffin and Span 80 are mixed as an oil phase, and the aqueous phase and the oil phase are stirred and mixed, and ultraviolet irradiation is performed during the stirring process; wherein the concentration of the SilMA solution is 10%-30%; the dissolution temperature of the SilMA dissolved in double distilled water is 25°C-45°C; the final concentration of the LAP aqueous solution is: 0.1%-0.5%; the volume ratio of the oil phase to the aqueous phase is 1:1-10:1; in the oil phase, the mass ratio of Span 80 to liquid paraffin is 1:10-1:30; the stirring temperature of the aqueous phase and the oil phase is 25°C-45°C; the stirring time and ultraviolet irradiation time are 5-15 minutes.

5. A ready-to-use mesoporous mineralized silk fibroin microsphere, characterized in that: The ready-to-use mesoporous mineralized silk fibroin microspheres are prepared by the preparation method described in any one of claims 1 to 4; in the ready-to-use mesoporous mineralized silk fibroin microspheres, the main component has a fiber structure, the microspheres have a mesoporous channel structure, and the surface of the microspheres includes a mineralized coating.

6. The ready-to-use mesoporous mineralized silk fibroin microspheres according to claim 5, characterized in that: The main component includes silk fibroin; the silk fibroin is silk fibroin methacrylamide.

7. The ready-to-use mesoporous mineralized silk fibroin microspheres according to claim 6, characterized in that: The mineralized coating is needle-shaped calcium phosphate; the pore size of the mesoporous channel is 5-50nm.

8. The ready-to-use mesoporous mineralized silk microspheres according to claim 7, characterized in that: The ready-to-use mesoporous mineralized silk microspheres are loaded with active proteins, which include any one or more of BMP-2, VEGF, FGF, and TGF-β.

9. A use of ready-to-use mesoporous mineralized silk fibroin microspheres for preparing a preparation for improving bone repair ability or promoting bone regeneration, characterized in that: The ready-to-use mesoporous mineralized silk fibroin microspheres are prepared by the preparation method described in any one of claims 1 to 4.

10. A use of ready-to-use mesoporous mineralized silk fibroin microspheres for preparing a preparation for improving the long-acting low-dose sustained release ability of BMP-2 or reducing the burst release ability of BMP-2, characterized in that: The ready-to-use mesoporous mineralized silk fibroin microspheres are prepared by the preparation method described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Preparation method and use of surface mesoporous silk fibroin microsphere drug slow-release carrier

    CN104825398A